Review of Polish and International Accounting Standards in Scope of Financial Instruments - Bakalarski, Tomasz (World Bank, Vienna, 2016)
Detailed principles of accounting for financial instruments have been prescribed in Financial Instruments Regulation, but some general principles in that area have also been outlined in the Accounting Act. According to article 3, paragraph 1, point 23 of the accounting act, financial instrument is defined as any contract giving rise to financial assets of one entity and a financial liability or an equity instrument of another entity, on condition that the contract concluded by two or more parties clearly results in economic effects, irrespective of whether the execution of contractual rights or obligations in unconditional or conditional. Financial assets include: monetary assets (assets in the form of domestic currency, foreign currencies and foreign exchange instruments and other financial assets, in particular accrued interest on financial assets, equity instruments issued by other entities, and contractual right to receive monetary assets or to exchange financial instruments with another entity under favorable conditions. Equity instruments are defined as contracts which give right to assets of an entity which remain after satisfying or securing all its creditors, as well as an obligation of an entity to issue or deliver its own equity instruments, in particular shares, share options or warrants.